Narratives of collaboration and resistance: Three anti-fascist novels written by women in the 1930s - Ronald Paul (Moderna Språk)
Throughout the 1930s, the impact of fascism on the role of women in society and in the family was the focus of several anti-fascist novels written by women. In this article I concentrate on three of the most significant and successful of these works in order to explore the way they dramatize the relationship between collaboration with and resistance to fascism. I show how they not only viewed the reactionary transformation of the state by fascist regimes as a historic defeat for women. They also sought to depict the effect this catastrophe had on their personal lives and how they coped with its social and political challenges. I have therefore selected the following novels – Storm Jameson’s In the Second Year (1936), Murray Constantine’s (Katharine Burdekin) Swastika Night (1937) and Phyllis Bottome’s The Mortal Storm (1938), since they address the fundamentally regressive nature of fascism in different ways as well as individual struggles against it. Moreover, they remain outstanding examples of anti-fascist fiction that still resonate with us today when the world is once more faced with the rise of rightwing, populist and neofascist parties.